INDOOR CONCENTRATIONS OF PM10/PM2.5 IN MARMARA UNIVERSITY LIBRARY, ISTANBUL - GÜNEŞ, GÜSSÜN (SCIBULCOM LTD, 2017)
Twenty-four-hour PM2.5 and PM10 samples were collected in the Marmara University Library Building, Istanbul, Turkey from January 5, 2014 to December 31, 2014. The ambient mass concentrations of PM2.5 and PM10 were determined by a gravimetric method. Interior environmental conditions can effect on library employees and users so the measured PM2.5 and PM10 concentrations were compared to national and international Air Quality Standards (EPA, EU, WHO), which were generally below the limit values. However, the limit values were exceeded during the exam periods. PM2.5 and PM10 concentrations were generally low in the summer. The number of library users in different rooms in the Marmara University Library was recorded and the user numbers also increased during the exam periods. The PM levels correlated well with the number of library users. Indoor PM values in the Marmara University Library Building were higher than the outdoor values in Umraniye, Istanbul during the exam periods; however they were lower in general. PM values in different libraries were lower than PM values in Marmara University Library Building. Healthy environment for employees and users in the library building can be provided by some measures such as the adequate heat and air-conditioning systems.
Keywords: indoor; particulate matter; library; AIR-QUALITY